Effects of genetic and non-genetic factors on growth traits of high yielding dairy seed calves and genetic parameter estimates (Journal of Advanced Veterinary and Animal Research, 2015)
The  study  was  conducted  to  know  the  effects  of several  genetic  and  non-genetic  factors  like  season, sex, year of birth, genotype of calves and milk yield of  dam  associated  with  growth  performance  of crossbred calves. Data were collected from registered farmers during the period of May, 2011 to April, 2013. Birth weight, three-month weight, six-month weight, weaning  weight  and  heritability  estimates  of  those growth performances were performed using a total of 82 registered calves which had pedigree information having the genotypes of 25% Local - 75% Friesian and 37.5% Local - 62.5% Friesian. The average birth, three-month, six-month and weaning weight of calves were 29.33,  64.32,  99.06  and  151.77  kg,  respectively.  The effects of non-genetic factors like sex, season of birth and  genotype  were  non-significant  (P>0.05)  for  the traits  birth weight, three-month, six-month, weaning weight  and  average  daily  gain  of  calves.  However, year of birth was found significant on birth (P